Development of a novel solvent extraction process using citric acid for lithium-ion battery recycling. (1st November 2021) - Punt, Tiaan; Akdogan, Guven; Bradshaw, Steven; van Wyk, Petrie
Highlights: Selective Al and Mn extraction from citrate LIB leach with D2EHPA at a pH of 2.5. Complete Mn extraction achieved in 3 counter-current stages. Novel Li separation from Co and Ni in citrate LIB leach with D2EHPA at a pH of 5.5. Metals effectively stripped and recovered from loaded D2EHPA with citric acid. Abstract: Recycling has become an important part of the lithium-ion battery (LIB) life cycle due to the growing demand for energy storage in applications like electric vehicles. Recycling spent LIBs provides a secondary source for strategically scarce metals, like lithium and cobalt, and reduces the environmental impact of toxic LIB waste. Citric acid has been proven to be an effective lixiviant that complexes with the LIB metals. Leaching spent laptop batteries with 1.5 M citric acid and 2 vol% H2 O2 at 95 °C, 20 g/L for 20 min achieved 93% Al, 90% Co, 96% Li, 94% Mn, and 94% Ni dissolution. The strong chelating property of citric acid affects the separation of the metals, requiring a unique extraction. The first extraction uses 12 vol% D2EHPA at a pH of 2.5 and O/A ratio of 2 to separate 99.9% Mn and 80% of the residual Al from the citrate leach solution in three counter-current stages. The second extraction then separates 94% Li in three counter-current stages using 23 vol% D2EHPA, O/A ratio 4, and pH 5.5. Both the manganese loaded organic and the lithium loaded organic were succesfully stripped using 1.5 M citric acid as stripping agent.